Pengaruh Media Sosial terhadap Pergeseran Bahasa Indonesia pada Mahasiswa Farmasi Universitas Nahdlatul Ulama Sunan Giri - Ainu Zuhriyah; Abdul Basith (Departement of Mathematics Education, 2023)
Advances in technology and information flow have made Indonesian people more open to global knowledge. It is undeniable that the development of the media also plays an active role in changing one's lifestyle, both electronic, print and online media. Judging from today's modern era, social media is not just a medium of communication, but has become part of human lifestyle, especially young people or students. One of the impacts of the advancement of technology with the existence of social media is a shift in language. Language shift is a linguistic phenomenon that sometimes refers to the extinction of a language. Social media is an online media where users can easily participate, share and create content including blogs, social networks and wikis, which are the most frequently used forms of social media by people around the world. 16 Social media is a website-based feature that can form networks. and enable people to interact within a community. On social media, we can carry out various forms of exchange, collaboration, and getting to know each other in the form of visual and audiovisual writing. Examples include Twitter, Facebook, blog, Forsquare, and others. Some of the problems found, researchers need to conduct research and the problem that is used in this study is how social media influences the shift in Indonesian among Pharmacy students at Nahdlatul Ulama Sunan Giri University. Social Media as a space for interaction can cause a shift in language, where the average pharmacy student at Nahdlatul Ulama Sunan Giri University or other students must understand this better and there is an increase in the knowledge of pharmacy students at Nahdlatul Ulama Sunan Giri University, especially regarding the influence of social media on language shift in pharmacy students at Nahdlatul Ulama University Sunan Giri.